# Expansion of (x + a)(x + b)(x + c)

We will discuss here about the expansion of (x + a)(x + b)(x + c).

(x + a)(x + b)(x + c) = (x + a){(x + b)(x + c)}

= (x + a){x$$^{2}$$ + (b + c)x + bc}

= x{x$$^{2}$$ + (b + c)x + bc} + a{x$$^{2}$$ + (b + c)x + bc}

= x$$^{3}$$ + (b + c)x$$^{2}$$ + bcx + ax$$^{2}$$ + a(b + c)x + abc

= x$$^{3}$$ + (a + b + c)x$$^{2}$$ + (bc + ab + ac)x + abc

= x$$^{3}$$ + (a + b + c)x$$^{2}$$ + (ab + bc + ca)x + abc

Therefore, (x + a)(x + b)(x + c) = x$$^{3}$$ + (Sum of the constant terms)x$$^{2}$$ + (Sum of the product of constant terms taking two at a time)x + Product of constant terms.

Solved Examples on Expansion of (x + a)(x + b)(x + c)

1. Find product of (x + 1)(x + 2)(x + 3)

Solution:

We know that, (x + a)(x + b)(x + c) = x$$^{3}$$ + (a + b + c)x$$^{2}$$ + (ab + bc + ca)x + abc

Here, a = 1, b = 2 and c = 3

Therefore, the product = x$$^{3}$$ + (1 + 2 + 3)x$$^{2}$$ + (1 ∙ 2 + 2 ∙ 3 + 3 ∙ 1)x + 1 ∙ 2 ∙ 3

= x$$^{3}$$ + 6x$$^{2}$$ + 11x + 6.

2. Find product of (x + 4)(x - 5)(x - 6)

Solution:

We know that, (x + a)(x + b)(x + c) = x$$^{3}$$ + (a + b + c)x$$^{2}$$ + (ab + bc + ca)x + abc

Here, a = 4, b = -5 and c = -6

Therefore, the product = x$$^{3}$$ + {4 + (- 5) + (- 6)}x$$^{2}$$ + {4 ∙ (-5) + (-5) ∙ (-6) + (-6) ∙ 4}x + 4 ∙ (-5) ∙ (-6)

= x$$^{3}$$ + (4  - 5 – 6)x$$^{2}$$ + (-20 + 30 – 24)x + 120.

= x$$^{3}$$ - 7x$$^{2}$$ - 14x + 120.

Problem on Expansion of (x + a)(x + b)(x + c)

1. Simplify the following by using standard formula and obtain the coefficients of x$$^{2}$$ and x.

(i) (x + 1)(x + 3)(x + 5)

(ii) (a + 2)(a – 4)(a + 6)

(iii) (2x + 1)(2x + 3)(2x + 5)

1. (i) x$$^{3}$$ + 9x$$^{2}$$ + 23x + 15

(ii) a$$^{3}$$ + 4a$$^{2}$$ – 20a - 48

(iii) 8x$$^{3}$$ + 36x$$^{3}$$ + 46x + 15

From Simplification of (x +)(x + b)(x + c) to HOME PAGE